(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
Preprocessing is one of the most important stages for facial recognition systems and therefore the analysis of data processing methods takes a major role for the upcoming work on the system. There are many methods that are unique in their own way and the choice of one of them depends on the task we choose.